PENGARUH MINAT BELAJAR, CARA BELAJAR DAN PENGGUNAAN WEB E-LEARNING UNP TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNP - Maisa Putri; Syamwil Syamwil; Rita Syofyan (Universitas Negeri Padang, 2018)
The problem of this research is the low of study result of Economic Education Student in Business English course. but there are several factors that influence learning outcomes. This study aims to analyze the influence of Learning Interests, How to Learn, and Use of Web E-Learning in Economic Education Students Faculty of Economics UNP.The type of research used is descriptive and quantitative. The population in this study amounted to 90 people. While the number of research samples determined based on Slovin formula as many as 73 people and selected by using proportional random sampling technique. The analysis technique used is multiple regression analysis, determination, F test and t test.The result of research shows 1) interest in learning, way of learning, and the use of E-Learning have a significant effect on the learning outcomes of students majoring in economics education in Business English courses 2) interest in learning have a significant effect on the students' learning achievement majoring in economic education in Business English, 3) how learning has a significant effect on the students 'learning achievement in the field of economics education in Business English, 4) the use of E-Learning has a significant effect on the students' achievement in economics education at the Business English course. Keyword: Interest learning, How to Learn, and Use of UNP E-Learning Web